Anti-Influenza Activity of 6BIGOE: Improved Pharmacological Profile After Encapsulation in PLGA Nanoparticles - Schroeder, Josefine; Westhoff, Jan; Vilotijević, Ivan; Werz, Oliver; Hoeppener, Stephanie; Löffler, Bettina; Fischer, Dagmar; Ehrhardt, Christina (International Journal of Molecular Sciences, 2025)
Influenza A virus (IAV) infections continue to threaten public health. Current strategies, such as vaccines and antiviral drugs, are limited due to their time-consuming development and drug-resistant strains. Therefore, new effective treatments are needed. Here, virus-supportive cellular factors are promising drug targets, and the encapsulation of candidate substances in poly(D,L-lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) is intended to improve their bioavailability. This study investigates the potential of the indirubin derivative 6-bromoindirubin-3′-glycerol-oxime ether (6BIGOE), a glycogen synthase kinase 3 (GSK-3)β inhibitor, for its potential to regulate IAV replication in vitro. The effects of 6BIGOE-loaded PLGA NPs on cell metabolism were assessed by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and lactate dehydrogenase (LDH) assays in A549 and Calu-3 cells. Viral replication and spread were monitored in various IAV-infected cell lines in the absence and presence of free and 6BIGOE-loaded PLGA NPs via plaque assays and Western blot analysis. The encapsulation of 6BIGOE in PLGA NPs resulted in reduced negative side effects on cell viability while maintaining antiviral efficacy. Both encapsulated and free 6BIGOE exhibited antiviral activity, potentially through GSK-3β inhibition and the disruption of key signaling pathways required for viral replication. The data indicate 6BIGOE, particularly after encapsulation in NPs, as a potential candidate for further investigation and development as an antiviral agent to treat IAV infections.
CRIS-Team Scopus Importer:2025-05-23
Keywords: antiviral; glycogen synthase kinase 3 (GSK-3); indirubin; influenza A virus (IAV); nanoparticles (NPs); poly(D; L-lactic-co-glycolic acid) (PLGA)